Hong Kong Landscapes : Shaping the Barren Rock - Owen, Bernie (Book collections on Project MUSE., 2007)
This book explains, in simple terms and with numerous photographs and figures, the origins of these varied landscapes, examining the contributions of different rocks, geological structures, and modern processes, as well as the profound impact of people.